Effectiveness of Tai Chi as a non-invasive intervention for mild cognitive impairment in the elderly: A comprehensive review and meta-analysis - Rampengan, Derren DCH.; Gunawan, Felicia A.; Rampengan, Jade AH.; Ramadhan, Roy N.; Iqhrammullah, Muhammad; Yufika, Amanda (Narra Sains Indonesia, 2024)
The aging population warrants the increase of mild cognitive impairment (MCI) prevalence, a condition that could progress to dementia. Efforts have been made to improve the MCI and prevent its progression, including the introduction of Tai Chi, a Chinese traditional exercise. The aim of this systematic review and meta-analysis was to evaluate the efficacy of Tai Chi in attenuating MCI among the elderly population. Records investigating the effect of Tai Chi exercise intervention on cognitive function among elderly patients were searched systematically from PubMed, ScienceDirect, Google Scholar, and Europe PMC as of April 13, 2023. The risk of bias (RoB 2.0) quality assessment was employed in the quality appraisal of the studies included. Review Manager 5.4.1 was used for data extraction and meta-analysis, where the standard mean difference (SMD) and 95% confidence interval (95%CI) were computed. Eight randomized control trials with a total of 1379 participants were included in this meta-analysis. Six trials assessed Montreal Cognitive Assessment scores, where its pooled analysis suggested that Tai Chi was as effective as conventional exercise (SMD=0.15, 95%CI: -0.11 to 0.40, p=0.26). However, pooled analysis of the Mini-Mental Status Examination suggested that Tai Chi intervention more effectively improved cognitive function and reduced the rate of cognitive impairment in elderly patients (SMD=0.36, 95%CI: 0.18 to 0.54, p<0.01) as compared to the control group. This systematic review and meta-analysis suggest that, in some extent, Tai Chi is efficacious in improving cognitive function and slowing down the rate of cognitive impairment among elderly patients.